How to Design Student Worksheet Based ELPSA Model to Improve Understanding of Mathematics Concepts? - Mayasari, Dian; Natsir, Irmawaty; Zulfiah, Mia (JTAM (Jurnal Teori dan Aplikasi Matematika), 2022)
Understanding of mathematics concept is the most important resolution in learning where students not only memorize the material but can understand and apply it in their daily lives. The ELPSA learning model can improve students' understanding of concepts through learning experiences, developing communication, presenting images in the form of visualizations, symbolizing in general terms, and as the application of the knowledge that has been obtained (application). This study aims to produce a product in the form of an ELPSA-based Student Worksheet that meets the criteria of being valid, practical, effective and has the potential to improve students' conceptual understanding. The method of this research is a 4D development model which is modified into 3D (Define, Design, and Develop). data collection instruments consist of observations, questionnaires and tests. This research produces valid, practical and effective student worksheets that can improve students' understanding of mathematical concepts. The results of this study indicate that the student worksheets are valid with good criteria. The student response questionnaire are 85.6% so it can be concluded that the student worksheets used are practical and can be used in learning. The effectiveness of obtaining a posttest average value of 87.06 with a percentage of 92.5% of students declared complete in learning. Student worksheets are said to be effective if student learning outcomes are declared complete. Mastery learning classically is said to be effective if it has reached 75% of the total number of students. Finally, student worksheets can improve students' understanding of mathematical concepts seen from the pretest and posttest questions that have been given. Student worksheets that have been applied can be a contribution for teachers to improve students' mathematical understanding in learning.